Pengaruh Penggunaan Media Pembelajaran Interaktif terhadap Motivasi Belajar Siswa pada Mata Pelajaran Ekonomi Kelas X di SMA Negeri 1 Telaga Kabupaten Gorontalo (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2025)
This study aims to examine the effect of using interactive learning media on students’learning motivation in Economics subjects for Grade X at SMA Negeri 1 Telaga,Gorontalo Regency. The study employs a descriptive quantitative approach, with a study population comprising Grade X students. A sample of 72 respondents was selected randomly using the cluster sampling teachnique, and an instrument test was conducted on 30 participants. The data analysis method applied is simple regression analysis, with validity tested using pearson correlation to determine whether the instrument is valid. The hypothesis was tested using the t-test. The findings of the study indicate that the use of interactive learning media significantly affect students’ learning motivation in Economics subjects for Grade X at SMA Negeri 1 Telaga, Gorontalo Regency. The study eyeats that interactive learning media contributes 43.8% to students’ learning motivation while the remaining 56.2% is influenced by other variables not exammed in this study.